Evaluasi Usability Pada Desain E-Learning Menggunakan Metode Cognitive Walkthrough - Febrian Alexander; Maria Bellaniar Ismiati (JuSiTik : Jurnal Sistem dan Teknologi Informasi Komunikasi, 2019)
This study conducted a study evaluating the usefulness of the UKMC Information System E-Learning design. The measurement uses three usability parameters namely efficiency, effectiveness, and satisfaction, satisfaction measurement uses the System Usability Scale (SUS). The sample in this study tested 28 users of E-Learning Information Systems and testing in this study used OBS (Open Broadcaster Software) software. Data processing is done quantitatively and qualitatively. The conclusion of the results of this study is that the dropbox menu needed improvement, namely validation of the data received and required maintenance from dokeos.